The Effects of Modern Architecture on the Evolution of Mosques in Sulaymaniyah - Ahmed Qadir Ahmed; Ihsan Fethi (Buildings)
Since the establishment of the Kurdistan Region Autonomy in 1991, extensive construction, including that of mosques, has reshaped the architectural environment. This phenomenon requires an examination of the evolved architectural features in new mosques and also raises questions about their alignment with the religious and symbolic objectives of mosque designs. This study focuses on the transformative impact of modern architectural styles on mosque evolution in Sulaymaniyah and uses an in-depth case study approach to analyze 23 contemporary mosques built over the past three decades. They blend traditional architecture with modern design principles, producing evolved features. The evolution in mosque designs raises questions about the alignment of new architectural features with the religious and symbolic objectives of mosque designs. This study employs indicator-based impact assessments to examine how modern features affect mosque evolution in terms of religious needs and mosque symbolism. Based on the literature of modern architecture and Islamic legitimacy, indicators of modern architecture and mosque design objectives were determined for further analysis. Then, the collected data from the field survey were analyzed through developed formulas. The results were converted to numerical values for use with the Pearson correlation coefficient, which identifies the causal relationship between modern architecture and design objectives. The results revealed that the overall influence of modern architecture on mosque evolution tends to be negative. Modern architectural styles have impacted mosques by increasing structural obstructions in 14%, reducing symbolic elements in 23%, and simplifying designs with fewer embellishments in 43% of all the cases. This study can assist decision-makers and designers in revising mosque design regulations; the issue has recently been the subject of ongoing debate in architects’ society.